2016
DOI: 10.21873/anticanres.11048
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Detection by Blue Dye Versus Indocyanine Green Fluorescence Imaging in Colon Cancer

Abstract: Abstract. Background In patients with colorectal cancer (CRC), the accurate establishment of the pathological status of tumor-draining mesenteric lymph nodes (LN) is of central importance for therapeutic management. In patients with stage III disease with demonstrated LN metastases, adjuvant systemic chemotherapy is indicated, reducing the risk of recurrence and improving long-term overall survival (1). The accuracy of mesenteric nodal staging depends primarily on the number of resected LN, and the seventh Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 21 publications
(32 reference statements)
0
45
0
1
Order By: Relevance
“…More recently, we have reported the results of a study using ex vivo ICG-FI for SLN detection in colorectal cancer and compared it with the standard blue dye technique. Although the sensitivity was higher for the ICG-FI technique in obese patient, the sensitivity of both techniques was low, 57% for ICG and 43% for the blue dye technique [15]. In this study, using ICG-FI after IV injection, the concept is completely different as the pathway used to visualize LNs is the systemic route.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 83%
“…More recently, we have reported the results of a study using ex vivo ICG-FI for SLN detection in colorectal cancer and compared it with the standard blue dye technique. Although the sensitivity was higher for the ICG-FI technique in obese patient, the sensitivity of both techniques was low, 57% for ICG and 43% for the blue dye technique [15]. In this study, using ICG-FI after IV injection, the concept is completely different as the pathway used to visualize LNs is the systemic route.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 83%
“…The ability of ICG NIR flouresence to detect metastatic LNs was compared with patent blue dye in one study. Liberale et al examined both techniques in 20 patients with colon cancer and reported that both techniques had the same detection rates (95%), yet with higher sensitivity in favor to ICG (57 vs 43%), especially in patients with BMI above 25 kg/m 2 . The overall correlation between the two techniques was greater than 80%.…”
Section: Discussionmentioning
confidence: 99%
“…Near‐infrared fluorescence imaging (NIR‐FI)‐guided surgery using indocyanine green (ICG), a non‐specific fluorophore, has been used as a new tool for sentinel lymph node (SLN) detection in various gynecological (breast, endometrium, cervix, ovary), digestive (colon, stomach), skin, and lung cancers . More recently, it has been reported that ex vivo ICG‐FI is able to detect metastatic LNs of colorectal and head and neck cancer origin .…”
Section: Introductionmentioning
confidence: 99%